The experience of comprehensive rehabilitation of a patient after a stroke with moya-moya disease. Case report - Elena V. Slyunkova; Anna A. Kondur (ZAO "Consilium Medicum", 2021)
The article describes a clinical case of neurorehabilitation with a multimodal approach of a young patient with repeated ischemic strokes against the background of a rare chronic progressive cerebrovascular disease moya-moya disease. The multimodal approach consisted in the use of high-tech complexes with biofeedback, such as a stabilometric platform for visual and support reactions, cognitive training using computer technologies, as well as mirror therapy, physiotherapy procedures and physical therapy, including physiotherapy exercises and individual targeted training with paretic limbs. In accordance with the clinical scales used, convincing data were obtained on the effectiveness of the selected complex of rehabilitation measures.